A systematic review of the prevalence and risk factors of irritable bowel syndrome among medical students - Ibrahim, Nahla Khamis (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Irritable bowel syndrome (IBS) represents a great challenge to public health, particularly among medical students. The aim of the study was to determine the global prevalence and risk factors of IBS among medical students. Materials and Methods: Data were obtained through searches in PubMed, Ovid, the Cochrane database, Embase, Google scholar, Institute for Scientific Information (ISI) “Web of Science,” and Medline from 1990 to June 2015. The search terms included “Irritable Bowel Syndrome” and “Medical students” and “prevalence, risk factors”. More than 100 articles were reviewed, scrutinized, and critically appraised for the eligibility criteria, and the relevant articles were selected. Results: Sixteen studies were identified, and the prevalence of IBS among medical students ranged from 9.3% to 35.5%. The relatively high prevalence among medical students may be attributed to their special stressful learning environment. Some studies found that female gender, family history of IBS, psychiatric stress, anxiety, depression, infections, dietary factors, and sleep disorders were associated with IBS. Conclusion: A relatively high prevalence of IBS was prevalent among medical students. Annual screening of IBS and introduction of stress management courses are recommended.